The ethical dimension of nursing care rationing: A thematic synthesis of qualitative studies - Vryonides, Stavros; Papastavrou, Evridiki; Charalambous, Andreas; Andreou, Panayiota; Merkouris, Anastasios (My University, 2015)
Background: In the face of scarcity, nurses may inevitably delay or omit some nursing interventions and give priority to others. This increases the risk of adverse patient outcomes and threatens safety, quality, and dignity in care. However, it is not clear if there is an ethical element in nursing care rationing and how nurses experience the phenomenon in its ethical perspective. Objectives: The purpose was to synthesize studies that relate care rationing with the ethical perspectives of nursing, and find the deeper, moral meaning of this phenomenon. Research design: A systematic review and thematic synthesis of qualitative studies was used. Searching was based on guidelines suggested by Joana Brigs Institute, while the synthesis has drawn from the methodology described. Primary studies were sought from nine electronic databases and manual searches. The explicitness of reporting was assed using consolidated criteria for reporting qualitative research. Nine studies involving 167 nurse participants were included. Synthesis resulted in 35 preliminary themes, 14 descriptive themes, and four analytical themes (professional challenges and moral dilemmas, dominating considerations, perception of a moral role, and experiences of the ethical effects of rationing). Discussion of relationships between themes revealed a new thematic framework. Ethical consideration: Every effort has been taken, for the thoroughness in searching and retrieving the primary studies of this synthesis, and in order for them to be treated accurately, fairly and honestly and without intentional misinterpretations of their findings. Discussion: Within limitations of scarcity, nurses face moral challenges and their decisions may jeopardize professional values, leading to role conflict, feelings of guilt, distress and difficulty in fulfilling a morally acceptable role. However, more research is needed to support certain relationships. Conclusions: Related literature is limited. The few studies found highlighted the essence of justice, equality in care and in values when prioritizing care—with little support to the ethical effects of rationing on nurses. Further research on ethical dimension of care rationing may illuminate other important aspects of this phenomenon.
Keywords: Care rationing; Ethical perspectives; Ethics; Nursing values; Professional role; Thematic synthesis